(untitled) (Circe de clásicos y modernos, 2018)
Taking into account thatthe inconsistencies between what we know about Seneca’s life and his philosophical tenets has been regarded as a central issue for the exegesis of the text, the present paper will try to show that the self-portrait that the epistolary ego presents in the first three books of the collection, and, additionally, the issues that these books thematize, aim at a redefinition, rectification or consolidation of certain aspects of Seneca’s previous ethos, as far as it is possible to reconstruct it from Tacitus’ account.